Eksplorasi Pengalaman Guru dan Siswa dalam Implementasi Literasi Keuangan di Sekolah Menengah Pertama di Jember: Pendekatan Grounded Theory - Dwi Ristantri, Citra; Cahyono, Dwi; Santoso, Budi; Susbiyani, Arik (Universitas Hamzanwadi, 2025)
This study aims to analyze the experiences of teachers and students in the implementation of financial literacy at school. The method used in this research is qualitative research with the Grounded Theory method, which aims to explore in depth the experiences of teachers and students in the implementation of financial literacy in schools. Data obtained from interviews and documentation through informants. The results of the study show that the implementation of financial literacy in junior high schools depends not only on the teaching materials provided, but also on interactive teaching methods, policy support and school resources, as well as family involvement in shaping students' financial habits. Therefore, to create a young generation with good financial literacy, a holistic approach involving various parties is needed, including teachers, schools, parents and students' social environment. Overall, the conceptual model developed in this study shows that the implementation of financial literacy in junior high schools cannot stand alone, but requires support from various parties, including schools, families, and the social environment